Hypophosphatemic Rickets in Patients from Bichoric Biamniotic Twins: A Case Report - Anna S. Nechaeva; Emma S. Grigoryan; Tatyana V. Turti; Tatiana E. Privalova; Nato D. Vashakmadze; Nina A. Krasnoshchekova (Педиатрическая фармакология)
Background. X-linked dominant hypophosphatemic rickets (X-linked hypophosphatemia, XLH) is a disease caused by mutations in the PHEX gene (located at the Xp22.1 locus), which encodes an enzyme bound to the cell surface that cleaves the protein phosphate-regulating neutral endopeptidase PHEX, predominantly expressed in osteoblasts, osteocytes and teeth. This is a rare genetic disease that has difficulties in early diagnosis, in which a multidisciplinary approach is important. Currently, a new targeted therapy has been developed, showing the first results. This article presents a case of familial X-linked hypophosphatemia.Case Report. Twin girls, premature babies, with low birth weight, having complications during the newborn period. There was low growth, late teething, delayed speech development, and varus deformity of the lower extremities in past medical history. A biochemical blood test showed an increase in the level of alkaline phosphatase, hypophosphatemia, and a decrease in the level of tubular phosphorus reabsorption. The characteristic signs of rickets were recorded on the X-rays. Phosphorous buffer preparations, the active form of vitamin D, were used in the treatment. The analysis of 166 genes responsible for bone pathology was carried out using high-performance parallel sequencing using the target panel “Hereditary diseases of the skeleton”, and a mutation in the PHEX gene was identified. At the age of 4 years and 8 months, a clinical diagnosis was established: X-linked dominant hypophosphatemic rickets. Heterozygous mutation c.1568+1G>A in the PHEX gene. Somatic stunting. Taking into account the O-shaped deformity of the legs, the girls underwent corrective osteotomy on the left tibia. At 6.5 years of age, haemiepiphysiodesis. At the age of 8, pathogenetic treatment with the preparation of monoclonal antibodies to fibroblast growth factor-23 — Burosumab, unregistered in the territory of the Russian Federation, was started. The dynamics of growth and laboratory data on the background of treatment is positive. Conclusion. Timely diagnosis of rare forms of rickets-like diseases is important to improve the quality of life of patients.